Integrated models for shipping a vendor’s final production batch to a single buyer under linearly decreasing demand for consignment policy - Omar, M; Supadi, S.S (Universiti Kebangsaan Malaysia, 2012)
This paper considers the problem of a vendor or manufacturer supplying a final production batch to a single buyer under linearly decreasing demand for a finite time horizon. The vendor manufactures the product at a finite rate and ships the output to the buyer. In this model we considered the case where the holding cost at the vendor is greater than the buyer and propose a consignment model. The objective was to minimize the total cost of stock transfer from vendor to buyer and stock holding at the vendor and the buyer. We derived the structure of the optimal solution and illustrate the proposed models with numerical examples.